Conceptual model of collaborative pharmaceutical practice in healthcare and social care for the elderly - Ilić, Velibor O.; Marinković, Valentina; Tasić, Ljiljana (Vojnosanitetski pregled, 2020)
Background/Aim. In the new millennium, the focus has been increasingly shifting to optimisation by enhancing the collaborative (common, joint) practice of healthcare professionals, for the purpose of achieving effectiveness and efficiency. Pharmacists are the last link in the healthcare services providing chain. The aim of this study was to present a critical analysis of the published models of the collaborative pharmacy practice along with development of a conceptual model of collaborative pharmacy practice in the healthcare and social care for the elderly population. Methods. Using two search algorithms that were created to search articles published in English, a comprehensive search of the bibliographic databases Web of Science and PubMed was undertaken (up to June 2015). Afterwards, articles were independently assessed by two authors, against predetermined inclusion and exclusion criteria. Results. Regulations on pharmacy collaboration are present in many developed countries. However, the implementation of the collaborative practice is still not widespread. Therefore, a conceptual model of the collaborative healthcare and social care of the elderly provides an insight into a multi-layer structure that has to be established in order to achieve a functioning system of the collaborative healthcare practice. The model concluded that aspirations towards teamwork, communication and above all – the system of regulators and payers, who acknowledge a healthcare collaboration, are crucial for establishment of a collaborative healthcare practice. Conclusion. This research provides a tool in the form of a guide and check-list for decision-makers and policy-makers in order to achieve the preferred effects generated from the collaborative practice by selecting the models and activities that need to be undertaken for implementation of the collaborative healthcare and social care of the elderly that is best suited for their country.
Keywords: delivery of health care; pharmacists; interdisciplinary communication; aged.